PENERAPAN STRATEGI EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF ARGUMENTATIF SMA WISUDA PONTIANAK - Diana Diana; Syambasril Syambasril; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis research is motivated problem class X High School Graduation Pontianak in writing argumentative paragraphs. The problem in this research is how the process and learning outcomes writing paragraph argumentative strategy here everyone is a teacher in class X High School Graduation Pontianak. The benefit of this study is to provide a foundation for other researchers to conduct research in the implementation of learning to write argumentative with using a different approach and language skills in general. Methods and forms used in this research is descriptive qualitative. The data source of this research is the Indonesian subject teachers and students of class X as many as 31 students. The data in this study is a learning process and results argumentative writing paragraphs. Data collection techniques are in the form of test and non test. Data collection tools in this study is in the form of tests, observation guidelines, and cameras. Data analysis techniques for analysis is the observation of the learning takes place. The results obtained from this study is the average value of student learning before using a strategy everyone is a teacher here is 50.00. Results of paragraph argumentative writing students in the first cycle was 69.22, but has not reached the expected KKM. Then proceed to the second cycle of the average value of students increased to 76,90.prosesnya using student worksheets and observation sheet attitudes. Keywords: Paragraph Argumentative, writing skill everyone is a teacher here